2016
DOI: 10.1016/j.jad.2015.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' wellbeing and depressive symptoms, and associated risk factors: A large cross sectional study in English secondary schools

Abstract: Wellbeing is low and depressive symptoms high amongst teachers. Interventions aimed at improving their mental health might focus on reducing work related stress, and increasing the support available to them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
175
6
23

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(212 citation statements)
references
References 42 publications
8
175
6
23
Order By: Relevance
“…Conversely, Kidger et al 16 found in their research in the United Kingdom low scores of well-being perception specifically among teachers. It is possible that such a difference, of higher well-being scores among the Brazilian population, is influenced by specific sociocultural characteristics of the country, since the wellbeing perception varies according to regional and socioeconomic characteristics 25 .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Conversely, Kidger et al 16 found in their research in the United Kingdom low scores of well-being perception specifically among teachers. It is possible that such a difference, of higher well-being scores among the Brazilian population, is influenced by specific sociocultural characteristics of the country, since the wellbeing perception varies according to regional and socioeconomic characteristics 25 .…”
Section: Discussionmentioning
confidence: 81%
“…The number of students per classroom was correlated to the burnout scores in the study of Carlotto and Palazzo (2006) 28 . In turn, Kidger et al 16 observed that lower well-being was associated with working in schools with higher requirement for tasks and performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of secondary school teachers reported alarming rates of depression (Kidger et al 2016). Teachers report that stress resulting from disruptive behaviour is central to burnout and exit from the profession (Kokkinos 2007).…”
Section: Editorial Emotional and Behavioural Difficulties And Mental mentioning
confidence: 99%
“…The disorders resulting from the musculoskeletal system can lead to the appearance of various signs, such as pain and functional incapacity, causing absence from work activities 4 . When excessive, stress can cause depression, psychological and physical exhaustion, and psychosomatic diseases 5 . In basic education, the quality of teaching is related to a qualified and motivated faculty 6 , therefore, it is essential to improve working conditions and avoid risk factors that negatively influence teachers' quality of life.…”
Section: Introductionmentioning
confidence: 99%